Penjualan Venue Melalui Pemasaran Digital Bagi Segmen Korporasi Pada Hotel Novotel Grand Shayla Di Makassar - Budianto, Muh. Annas; Ab., Ahmad; Islahuddin, Islahuddin; Hanafi, Hamsu (Program Studi Manajemen Divisi Kamar, 2026)
This research was conducted at the Novotel Grand Shayla Hotel in Makassar, with the aim of identifying and analyzing the experiences of marketing staff in marketing venues through digital media, as well as analyzing the extent to which the optimization of these strategies is able to effectively reach the corporate segment. The method used was a qualitative descriptive approach, employing data collection techniques such as in-depth interviews with Sales and Marketing staff, as well as documentation. The research findings indicate that the Sales and Marketing team has implemented seven main digital strategies, including: creating visual content, utilizing social media (Instagram, Facebook, WhatsApp), e-mail marketing via Mailchimp, the CVENT marketplace platform, strengthening SEO through Yext, analyzing data insights, and paid advertising through Meta Business. Although digital approaches have been actively implemented, the content strategies applied remain general and have not been specifically segmented for the corporate segment. Additionally, TikTok has not been utilized despite its potential as a promotional channel for venues targeting young professional audiences. Therefore, the findings of this study are expected to provide insights for hotel management in optimizing more effective and focused digital marketing strategies tailored to the corporate segment.